2017
DOI: 10.9773/sosei.58.66
|View full text |Cite
|
Sign up to set email alerts
|

Residual Deflection Mechanism for Back-Up Roll Consisting of Shrink-Fitted Sleeve and Arbor

Abstract: First, back-up rolls for rolling require toughness, particularly in the shaft portion, and high-hardness in the sleeve portion. The back-up rolls are classified into two types; one is a single-solid type, and the other is a shrink-fitted construction type consisting of a sleeve and an arbor. The shrink-fitted back up roll has several advantages, for example, different materials can be chosen and the arbor can be reused by replacing the damaged sleeve. Therefore, the shrinkfitted back-up rolls are economical. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…In the previous study, 4) Noda et al have studied the relationship between slippage and residual deflection in axial direction for the back-up roll composed of the shrink-fitted sleeve and the shaft. They have indicated that the residual deflection is similar to the relative slippage between the sleeve and the shaft.…”
Section: Slippage Zone Of Shrink-fitting Surface and Residual Displacmentioning
confidence: 99%
See 2 more Smart Citations
“…In the previous study, 4) Noda et al have studied the relationship between slippage and residual deflection in axial direction for the back-up roll composed of the shrink-fitted sleeve and the shaft. They have indicated that the residual deflection is similar to the relative slippage between the sleeve and the shaft.…”
Section: Slippage Zone Of Shrink-fitting Surface and Residual Displacmentioning
confidence: 99%
“…From the stress distributions τ rθ and μσ r along the shrink-fitted surface, they have discussed the relative slippage condition. 4) Eventually, they have reported that the stress quasi-equilibrium region τ rθ ≅ | μσ r | at the shrink-fitted surface causes the residual deflection. In this research, the slippage in the circumferential direction is targeted, and the slippage direction differs from the study by Noda et al (axial slippage).…”
Section: Slippage Zone Of Shrink-fitting Surface and Residual Displacmentioning
confidence: 99%
See 1 more Smart Citation
“…Rolling technology is developing and advancing further although seemingly mature. [ 1–13 ] Figure 1 shows the rolling roll in roughing stands of hot rolling stand mills. By replacing the conventional single‐material rolls, bimetallic work rolls are developed through improving wear resistance and heat crack resistance.…”
Section: Introductionmentioning
confidence: 99%